2019
DOI: 10.3390/ijerph17010007
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Risk Factors of Type 2 Diabetes Mellitus (DMT2) in a Semi-Urban Saudi Population

Abstract: (1) Background: Diabetes mellitus is a common health problem in Saudi Arabia, causing a huge burden for individuals, families, and communities. The objectives of the current study were to determine the prevalence and risk factors of type 2 diabetes mellitus among a semi-urban population of Saudi Arabia. (2) Research methods: The research design was cross-sectional, and the research was conducted in five primary health care centers (PHCC) in Majmaah, Saudi Arabia. The sample size was calculated as 353. A pre-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 35 publications
7
59
0
11
Order By: Relevance
“…[ 5 6 7 ] A recent Saudi study found obesity and overweight among the high prevalence and risk factors of T2DM. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 6 7 ] A recent Saudi study found obesity and overweight among the high prevalence and risk factors of T2DM. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization states that the number of people with diabetes will double in the next ten years [ 1 ]. Generally, T2DM is a multifactorial chronic endocrine disorder [ 2 ] manifested by hyperglycaemia. This condition is caused by increased hepatic glucose production, lower insulin secretion, and impaired insulin action [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies have also revealed that females have a higher risk of developing diabetes than males. It was due to the female's physical activity was lower than in males, resulting in body fat accumulation that triggers obesity (Abdullah and Mansour, 2020;Agbogli and Annan, 2017;Asiimwe et al, 2020;Eze et al, 2014). Furthermore, it is associated with an enhanced risk of developing insulin resistance and ultimately causing the T2DM (Mary et al, 2014).…”
Section: Results and Discusionmentioning
confidence: 99%